2020
DOI: 10.21608/pssjn.2020.94767
|View full text |Cite
|
Sign up to set email alerts
|

Self Care Practices of Patients With Lumbar Disc Prolapse in the Postoperative Period

Abstract: Background: Self care practices affect the progress of many diseases including lumbar disc prolapse. This study aimed to assess self care practices of patients with lumbar disc prolapse in the post operative period. Setting: This study conducted at neuro-surgery department and outpatient clinic at Azhar university hospital in New Damietta city. A convenience sample of 124 adult patients diagnosed with lumbar disc prolapse were included in the study. Tool of data collection: data collected using structured inte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 10 publications
1
2
0
Order By: Relevance
“…The finding of the present study in the same context with Ahmed et al (14) in the study entitled "Self-Care Practices of Patients with Lumbar Disc Prolapse in The Postoperative Period", stated that, less than one-third of studied patients were at age 30 to less than 40 years old and the same proportion was from 40 to less than 50 years old. But on the other hand, Abbady et al (17) in the study entitled "Assessment of Daily Living Activities among Elderly Patient with Low Back Pain at Ministry Health Hospitals", founded that, the mean age of the studied patients ranged between 60 and 80 years with mean 64.89 ± 4.64 years.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…The finding of the present study in the same context with Ahmed et al (14) in the study entitled "Self-Care Practices of Patients with Lumbar Disc Prolapse in The Postoperative Period", stated that, less than one-third of studied patients were at age 30 to less than 40 years old and the same proportion was from 40 to less than 50 years old. But on the other hand, Abbady et al (17) in the study entitled "Assessment of Daily Living Activities among Elderly Patient with Low Back Pain at Ministry Health Hospitals", founded that, the mean age of the studied patients ranged between 60 and 80 years with mean 64.89 ± 4.64 years.…”
Section: Discussionsupporting
confidence: 83%
“…After treatment, patients with lumbar disc prolapse may experience numerous consequences that could result in disability from poor self-care practices. For lumbar disc prolapse, post-operative self-management along with patient education regarding continuing physical activity as tolerated has been recommended for lumbar disc prolapse (14) .…”
Section: Significance Of the Studymentioning
confidence: 99%
“…Women with spine pathology are more likely to experience sexual dysfunction than men, with a ratio of 10:6 8 . Reports on sexual dysfunction and lumbar disc herniation (LDH) are predominantly focused on men, which is attributed to challenges in discussing sexual performance with female patients 22 , 23 . As no specific study on the sexual performance of women with LDH was found, statistics related to men's studies or combined results of men and women were included for discussion.…”
Section: Discussionmentioning
confidence: 99%